Stellar 78, 80, 84, 86Kr(n, γ) Reactions Studied by Activation at SARAF-LiLiT, Atom Trap Trace Analysis and Decay Counting. (October 2020) - Tessler, M.; Paul, M.; Weissman, L.; Zappala, J.; Baggenstos, D.; Halfon, S.; Heftrich, T.; Jiang, W.; Kreisel, A.; Lu, Z.; Mueller, P.; Purtschert, R.; et al.
Abstract: We report on (n, γ) neutron capture experiments performed with the Liquid-Lithium Target (LiLiT) and the mA-proton beam at 1.92 MeV (2-3 kW) from the Soreq Applied Research Accelerator Facility (SARAF). The setup yields high-intensity 30-keV quasi-Maxwellian neutrons (3-5 × 10 10 n/s) closely reproducing the conditions of s -process stellar nucleosynthesis. The 78, 80, 8486 Kr(n, γ) reactions at the border between weak- and strong- s -process were studied. A Ti sphere filled with 107.7 mg of natural Kr gas was placed in an irradiation chamber downstream of LiLiT with a gold foil used as a neutron fluence monitor during the activation. The activities of the short-lived Kr isotopes ( 7985m87 Kr) were measured by γ decay counting with a HPGe detector. The long-lived Kr isotopes ( 81, 85 gKr) were measured by atom counting via Atom Trap Trace Analysis (ATTA) at Argonne and Low-Level Counting (LLC) at Bern.